IMPLEMENTATION OF THE MOORA METHOD DETERMINING THE FEASIBILITY OF SAVING AND LOANS CONCEPT - Novi Trisna; Raja Ayu Mahessya; Yesri Elva (Jurnal Ipteks Terapan, 2023)
The savings and loan cooperative “Doni Jaya Cooperative” is a savings and loan cooperative that provides solutions in helping to provide funds for various needs quickly and with an easy loan process. Associated with the loan process, many credit applicant members often complain that the credit application process is long and too convoluted. Currently, the maximum time limit from the registration stage to the credit realization stage, set by the Doni Jaya Cooperative, is a maximum of 7 (seven) working days. There are many credit arrears originating from borrowers. The increase in the ratio of delinquent loans has forced the Doni Jaya Cooperative to be more careful and selective in extending credit to its members, while the Doni Jaya Cooperative is required to cover the credit realization target every month. By applying the MOORA method in determining the recipient of a revolving capital loan at the Doni Jaya Cooperative, it makes it easier for the Cooperative to speed up the process of determining which loan recipients are eligible to get a revolving capital loan